2020
DOI: 10.1002/he.20365
|View full text |Cite
|
Sign up to set email alerts
|

A Field of Striving or Equity? Regional Public Universities and College Access

Abstract: Many regional public universities (RPUs) provide college access to diverse groups of undergraduate students and face pressures to pursue prestige in the academic hierarchy. Prior research posits that RPUs will strive for prestige because of status-and resource-based rewards that flow from increasing their admissions selectivity, research-intensity, and wealth. As this dominant perspective suggests, RPUs may erode historic missions of democratizing educational opportunity to emulate their more elite peers to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…An increase in the percentage of enrolled federal Pell Grant recipients (a proxy for low-income students) was associated with small upticks in enrollment share of URM students and in the diversity index score. This relationship is consistent with prior research highlighting mission-driven PMIs that serve local, historically marginalized students (Fryar, 2015;McClure, 2018;Oprhan, 2018Oprhan, , 2020Warshaw et al, 2020Warshaw et al, , 2021. We also found that an increase in international student enrollment was associated with a decrease in URM enrollment share and an increase in the diversity index score.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An increase in the percentage of enrolled federal Pell Grant recipients (a proxy for low-income students) was associated with small upticks in enrollment share of URM students and in the diversity index score. This relationship is consistent with prior research highlighting mission-driven PMIs that serve local, historically marginalized students (Fryar, 2015;McClure, 2018;Oprhan, 2018Oprhan, , 2020Warshaw et al, 2020Warshaw et al, , 2021. We also found that an increase in international student enrollment was associated with a decrease in URM enrollment share and an increase in the diversity index score.…”
Section: Discussionsupporting
confidence: 91%
“…PMIs are thus "comprehensive" in offering undergraduate and masters' programs, as well as some doctoral degrees, in areas matching local workforce needs. As such, they enhance access and social mobility for underrepresented minoritized (URM) students and provide critical boons to equity in higher education and society as a whole (Chetty et al, 2017;de Alva, 2019;McClure, 2018;Warshaw et al, 2020Warshaw et al, , 2021.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While governments and universities often emphasize the potential benefits of enhancing research prestige, striving often involves trade-offs (O'Meara, 2007), and can lead to unintended consequences pertaining to institutional mission, quality, and equity (Ryan, 2019;Warshaw et al, 2020). In particular, because the productivity of faculty plays a central role in determining the institutional prestige of universities, it is likely that striving will push institutions to recruit and retain scholars with the highest level of status and reputation.…”
mentioning
confidence: 99%